2006
DOI: 10.1111/j.1095-8649.2006.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of mangroves, mud and sand flats, and seagrass beds as feeding areas for juvenile fishes in Chwaka Bay, Zanzibar: gut content and stable isotope analyses

Abstract: The relative importance of bay habitats, consisting of mangrove creeks and channel, seagrass beds, and mud and sand flats, as feeding grounds for a number of fish species was studied in Chwaka Bay, Zanzibar, Tanzania, using gut content analysis and stable isotope analysis of carbon and nitrogen. Gut content analysis revealed that within fish species almost the same food items were consumed regardless of the different habitats in which they were caught. Crustaceans (mainly copepods, crabs and shrimps) were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 54 publications
3
74
2
2
Order By: Relevance
“…The connectivity between mangrove forests and the adjacent ecosystems for the ichthyofauna has already been elucidated by several studies and evidence from the overlaps in carbon and nitrogen signatures of fish collected in these different environments (Nagelkerken et al, 2012;Igulu et al, 2013;Kimirei et al, 2013). These isotopic signatures suggest that juvenile and/or adult fish probably choose more than one habitat to feed, find shelter or both (Lugendo et al, 2006(Lugendo et al, , 2007. Their movements may be triggered by several factors: tides, food availability, variation in salinity and/or ontogeny (Cocheret de la Morinière et al, 2003;Lugendo et al, 2005Lugendo et al, , 2006Nakamura et al, 2008;Kimirei et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connectivity between mangrove forests and the adjacent ecosystems for the ichthyofauna has already been elucidated by several studies and evidence from the overlaps in carbon and nitrogen signatures of fish collected in these different environments (Nagelkerken et al, 2012;Igulu et al, 2013;Kimirei et al, 2013). These isotopic signatures suggest that juvenile and/or adult fish probably choose more than one habitat to feed, find shelter or both (Lugendo et al, 2006(Lugendo et al, , 2007. Their movements may be triggered by several factors: tides, food availability, variation in salinity and/or ontogeny (Cocheret de la Morinière et al, 2003;Lugendo et al, 2005Lugendo et al, , 2006Nakamura et al, 2008;Kimirei et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These isotopic signatures suggest that juvenile and/or adult fish probably choose more than one habitat to feed, find shelter or both (Lugendo et al, 2006(Lugendo et al, , 2007. Their movements may be triggered by several factors: tides, food availability, variation in salinity and/or ontogeny (Cocheret de la Morinière et al, 2003;Lugendo et al, 2005Lugendo et al, , 2006Nakamura et al, 2008;Kimirei et al, 2013). Mangroves may, therefore, be designated as potential nurseries for pelagic and demersal coral reef fish and crustaceans (Laegdsgaard & Johnson, 2001;Nagelkerken et al, 2002;Nagelkerken, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This largely zoobenthivorous fish species typically occurs as juveniles in seagrass beds and mangroves, which provide shelter (Igulu et al 2011) and feeding areas (Lugendo et al 2006), whereas the adults are predominantly found on coral reefs (Kimirei et al 2011). Experimental fish were caught daily in a tidal pool at an average depth of 0.4 m (Fig.…”
Section: Fish Collection and Choice Chamber Designmentioning
confidence: 99%
“…Estuaries are recognised for encompassing a variety of habitats, including mangrove swamps, algal banks, and mudflats (TSE et al, 2008), with vegetated habitats exhibiting greater fish abundance and species richness than non-vegetated habitats (LUGENDO et al, 2006). This pattern is the result of the greater structural complexities and resources that develop on a vegetated substrate, providing greater protection from predators and increased food availability (WANG et al, 2009).…”
Section: Introductionmentioning
confidence: 99%